Influence of consumer socio-psychological food environment on food choice and its implications for nutrition: evidence from Tanzania - Mushi, Eward; Alphonce, Roselyne; Waized, Betty; Muhanga, Mikidadi; Khalili, Niloofar; Rybak, Constance (Frontiers in Nutrition, 2025)
BackgroundChanges in consumer food choices have been associated with transformation in the food environment. Despite the direct impact of consumers' food choices on their diet and health outcomes, there is a lack of comprehensive evidence regarding how various factors within the food environment impact these choices.MethodsThis study uses the Theory of Planned Behavior to examine how socio-psychological factors in the food environment influence consumers' healthy food choices. A survey of 714 randomly selected adult consumers was conducted in selected rural and urban areas in Tanzania. Data was analyzed using structural equation modeling.ResultsThe results indicate that consumers' knowledge, attitudes, and perceived behavioral control significantly explain 93% of the variance in the intention to choose healthy foods. The intention to choose healthy foods was found to be positive and significantly associated with the consumption of fruits and vegetables. Moreover, background factors, namely age, gender, location, and income, significantly influence the intention and actual behavior of healthy eating. Notably, the intentions of female and urban consumers to choose healthy foods do not converge with their consumption patterns of fruits and vegetables.ConclusionThese findings indicate that socio-psychological factors within the personal food environment are key determinants of food choice behavior. Thus, integrating consumers' socio-psychology into the food environment, as well as nutrition-sensitive and nutrition-specific interventions, can enhance consumers' knowledge of food choice and foster positive attitudes and perceptions regarding healthy eating. Food and health literacy programs could serve as effective strategies for achieving healthy eating behavior.